Unveiling the COVID-19 Recession: The Effect of Sectoral Exposure on the Economy and Labor Market - Handayani, Fitri (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: The impacts of the COVID-19 pandemic on economic and labor market conditions still need further research. This is because the pandemic had different and more extensive impacts than the 2008 global financial crisis. Background Problems: The lack of studies that explore the sectoral exposure of the economic and labor market to COVID-19 motivates this study to examine the problems and determine the impacts of the pandemic on the economy and labor market heterogeneity. Novelty: The sectoral exposure classification was based on sectoral risk and teleworkability indicators. Furthermore, input-output tables are used to analyze the interregional economic linkages based on economic activities in terms of sectoral exposure. To the best of the author’s knowledge, this is the first study to explore the topic in Indonesia. Research Methods: The data used are a cross-section of 34 provinces in 2020. This study uses input-output tables to examine the relationship between sectoral exposure and the economy. In addition, regression analysis is used to examine the effect on the labor market. Finding/Results: The industry categorized as having medium-high sectoral exposure is the key sector in Indonesia because the forward and backward linkage has a value of more than 1. It means medium-high sectoral exposure greatly affects other industries' input and output. According to the OLS result, sectoral exposure significantly impacts short-time workers and the unemployment rate. Conclusion: This study implies that sectoral exposure to COVID-19 was significant for Indonesia's economic and labor market.